Consumer Purchasing Decisions in Review of Digital Marketing, Product Quality, and Location at Anugrah Farm Kediri Cow's Milk - Gymnastiar, Elang Maulana; Leksono, Poniran Yudho (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study is to examine how Anugrah farm purchasing decisions are impacted by digital marketing, product quality, and location. Design/Method/Approach: This study uses multiple linear regression analysis as part of a quantitative methodology.  Using the Accidental Sampling technique, 30 respondents were given questionnaires to complete in order to collect data. Research Finding: The results showed that partially Digital Marketing, Product Quality, and Location have a significants influence on purchasing decisions. Simultaneously, the three variables also influence purchasing decisions with an Adjusted R² value of 81.0%.  Theoretical contribution/Originality: This research adds insight into the importance of Digital Marketing, Product Quality, and Location as strategic factors in influencing purchasing decisions, especially in the small and medium enterprise sector engaged in fresh milk production.  Practitionel/Policy implication: Anugrah Farm can increase sales by utilizing more digital platforms such as TikTok, improving product quality through standardization, and considering distribution locations to expand the market.  Research limitation: The results of this study cannot be broadly extrapolated because it only uses three independent variables and a small sample size.  It is advised that more study be done to include additional factors like price and promotion.